2004
DOI: 10.1136/hrt.2003.011114
|View full text |Cite
|
Sign up to set email alerts
|

Implications of plasma concentrations of adiponectin in patients with coronary artery disease

Abstract: Objective: To investigate whether concentrations of plasma adiponectin constitute a significant coronary risk factor, with particular focus on the relation between plasma concentrations of adiponectin and the development of acute coronary syndrome (ACS). Subjects and methods: Plasma concentrations of adiponectin were measured in 123 patients with coronary artery disease (CAD) and in 17 control participants. Patients were divided into three groups according to condition type: acute myocardial infarction (AMI) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
135
7
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(173 citation statements)
references
References 34 publications
22
135
7
9
Order By: Relevance
“…These previous studies did not focus on patients with CAD. Our results not only confirm these findings but also extend them to CAD patients, a population known to have significantly lower adiponectin levels than subjects without CAD (16,27). Mean and median adiponectin levels in our study group were lower than reported in previous studies (6 -8, 10), but similar to the levels reported in a recent study of patients with acute myocardial infarction, many of whom were found to have IFG and previously undiagnosed DM (3).…”
Section: Discussioncontrasting
confidence: 40%
“…These previous studies did not focus on patients with CAD. Our results not only confirm these findings but also extend them to CAD patients, a population known to have significantly lower adiponectin levels than subjects without CAD (16,27). Mean and median adiponectin levels in our study group were lower than reported in previous studies (6 -8, 10), but similar to the levels reported in a recent study of patients with acute myocardial infarction, many of whom were found to have IFG and previously undiagnosed DM (3).…”
Section: Discussioncontrasting
confidence: 40%
“…6 In young survivors (o60 years of age) following a first myocardial infarction, however, a low plasma adiponectin level was associated with recurrent infarction. 7 Indeed, hypoadiponectinemia has usually been recognized as a risk factor for CAD [8][9][10] and the adiponectin level was linked to the severity of heart failure in our previous study. 11 Taken together, it seems that the plasma adiponectin level may influence cardiovascular or cerebrovascular events but not decisively, because the adiponectin level varies in relation to gender, race and the presence or absence of lifestyle-related disease.…”
Section: Introductionmentioning
confidence: 83%
“…First, a low adiponectin level was not associated with cerebral hemorrhage or infarction after adjusting for other cardiovascular risk factors in the JMS cohort study that was performed in 12 rural districts in Japan, 12 and that the finding corresponds with the present result that the plasma adiponectin level is not related to cerebrovascular events. Second, Persson et al 7 reported that low plasma adiponectin levels are associated with myocardial infarction in individuals below the age of 60 years, and Nakamura et al 10 found that hypoadiponectinemia may increase the risk of acute coronary syndrome. Furthermore, in a study of Japanese men with CAD, patients with acute coronary syndrome had lower adiponectin levels than stable CAD patients, whereas patients with multiple complex lesions had significantly lower adiponectin levels than those with solitary complex lesions.…”
Section: Discussionmentioning
confidence: 99%
“…It positively regulates glucose and lipid metabolism, and has multiple anti-inflammatory effects [22]. Epidemiological studies confirmed the low circulatory levels of adiponectin in CAD [23,24]. Adiponectin participates in the in vivo clearance of apoptotic cellular bodies and blebs of dying cells by binding them, leading to phagocytosis by monocyte derived macrophages, thereby minimizing tissue injury and inflammation [25,26].…”
mentioning
confidence: 92%